The Holy See and the Crimean Crisis (1853-1856): The Menacing Savoy’s Expansionism - Battaglia, Antonello (Richtmann Publishing, 2012)
At the beginning of the Crimean War, the Holy See played a major role in the international policy debate. The Pope Pius IXtook an ambiguous policy by putting pressure on the continental powers to declare war against the Orthodox Russian Empire of NicholasI, but at the same time he didn’t want that Austria took part in the war.The apparent contradictory papal policy hides a coherent project:defeating Russian Empire, its expansionism and asserts the Roman’s superiority over the orthodox faith, but at the same time Austriamust not act because Vienna is the order’s guarantor in Italian peninsula. If Austrian Emperor goes to war, he’ll remove his men from theLombard-Venetian front sending them to the east and, especially, this situation can be an opportunity for the Kingdom of Sardinia’sexpansionism or for Italian revolutionaries to destabilize the peninsula and also Holy See’s territorial integrity. This is the position of thepontifical diplomacy at the beginning of the War.